A marginal anticancer effect of regorafenib on pancreatic carcinoma cells in vitro, ex vivo, and in vivo - Eckel, Barbara; Karakhanova, Svetlana; Bauer, Nathalie; Liu, Li; Bazhin, Alexandr V. (Naunyn-Schmiedeberg's archives of pharmacology, 2017)
Activation of receptor tyrosine kinases is recognized as a hallmark of cancer. Vascular endothelial growth factor (VEGF) and its receptor VEGFR are the prominent players in the induction of tumor neoangiogenesis. Strategies to inhibit VEGF and VEGFR are under intensive investigation in preclinical and clinical settings. Regorafenib is a multikinase inhibitor targeting some VEGFR and other receptor kinases. Preclinical results led to the FDA approval of regorafenib for treatment of metastatic colorectal cancer patients. Effects of this drug in pancreatic ductal adenocarcinoma (PDAC) have not been investigated yet. Gene expression was assessed with real-time PCR analysis. In vitro cell viability, proliferation, apoptosis, necrosis, migration, and invasion of the PDAC cells were assessed after regorafenib treatment. Ex vivo anti-tumor effects of regorafenib were investigated in a spheroid model of PDAC. In vivo anti-tumor effects of the drug were evaluated in a fertilized chicken egg model. In this work, we have demonstrated only a marginal anticancer effect of regorafenib in PDAC in vitro and ex vivo. However, in the egg model of PDAC, this drug reduced tumor volume. Besides, regorafenib is capable of modulating the expression of cancer stem cell (CSC) markers and epithelial-to-mesenchymal transition (EMT) markers on PDAC cells. We found out that effects of regorafenib on the expression of CSC and EMT markers are very heterogeneous and depend obviously on original expression of these markers. We concluded that regorafenib might be a potential drug for PDAC and it should be investigated in future clinical trials.